Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
:Table of Content • A teaching program based on experiential learning and its effectiveness in developing strategic competence and productive thinking in the mathematics curriculum among sixth-grade students in Hail Dr. Howishel Saud Alhowishel • The Role of Incentives Used by Teachers on the Achievement of Autistic Students in East Jerusalem Schools from Teachers’ Perspective Ms. Nancy Mohammed Abdelsalam Issa , Ms. Amal Sami Ahmad Abdel-Rabu • The Degree of Use of Digital Content Design Applications by College of Humanities Students in the Distance Learning and Teaching Strategies Course Ms. Nouf Farhan Alenazi , Ms. Nada AbdulAziz Al-Mashouq ,Prof. Mona Abdullah Al-Bisher • The Reality of Implementing Voluntary Hours in the Tracks System in Secondary Schools in the Northern Border Region from the Students’ Perspective and Its Impact on Their Career Maturity Mr. Talal Glub Alshammary , Prof. Fahd Abdul-Aziz Abanmi • The effectiveness of employing digital games on First-Grade Students’ Achievement improving the academic achievement of first-grade students in mathematics and enhancing their motivation to learn. Qualitative Study from parents’ perspectives Ms. Anan Shaker Hamdan • The Extent to Which Social Studies Teachers Employ Lateral and Design Thinking in Architectural Education: An Exploratory Study from Their Perspective Dr. Zouwaina Khalaf Al-Ghawi, Dr. Noor Ahmed Al Najar • Insights into the Reflection of Oman Vision 2040’s Priorities and Strategic Directives in the Newly Introduced ELT Textbook Series “Team Together Oman”: Content Analysis and Teachers’ Perspectives Ms. Salama Saif Hamed Al-Siyabi, Ms. Khadija Mohammed Nasser Al-Harthi